2019
DOI: 10.1002/ehf2.12435
|View full text |Cite
|
Sign up to set email alerts
|

A 79‐year‐old woman with atrial fibrillation and new onset of heart failure

Abstract: As an alternative to oral anticoagulation, percutaneous left atrial appendage (LAA) closure is an increasingly performed procedure to prevent arterial embolism in patients with non‐valvular atrial fibrillation. Besides procedure‐related complications, residual leaks, device‐related thrombus formation, and dislocation of the LAA occluder have been observed during follow‐up. Heart failure as a consequence of interventional LAA closure has not been reported so far. This case report describes a 79‐year‐old lady wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is still unclear if there are long-term effects from "removing" a cavity in the LA. Some studies have suggested heart failure deterioration may be caused by LAA exclusion, 58 due to the reduction of atrial and brain natriuretic peptide secretion. In addition, several animal experiments 59 show LAA removal led to reduction in left atrial compliance (and thus, reservoir function), cardiac output, stroke volume, and even water retention, all factors that could promote heart decompensation, particularly those with restrictive physiology.…”
Section: Instrumentation/implantationmentioning
confidence: 99%
“…It is still unclear if there are long-term effects from "removing" a cavity in the LA. Some studies have suggested heart failure deterioration may be caused by LAA exclusion, 58 due to the reduction of atrial and brain natriuretic peptide secretion. In addition, several animal experiments 59 show LAA removal led to reduction in left atrial compliance (and thus, reservoir function), cardiac output, stroke volume, and even water retention, all factors that could promote heart decompensation, particularly those with restrictive physiology.…”
Section: Instrumentation/implantationmentioning
confidence: 99%
“…7,8 In contrast, the LAA has the reservoir function of absorbing pressure and distending its chamber when LA volume and pressure rises; 9 therefore, exclusion of the LAA may result in unfavorable LA pressure-volume relations and worsening LA compliance. 10 However, the development and aggravation of heart failure (HF) was not consistently assessed in previous trials on LAAO. The purpose of this study was to identify the predictors of subsequent HF after successful LAAO.…”
mentioning
confidence: 99%